2011
DOI: 10.1002/dneu.20864
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment influences neuronal stem cells in the adult crayfish brain

Abstract: New neurons are incorporated throughout life into the brains of many vertebrate and non-vertebrate species. This process of adult neurogenesis is regulated by a variety of external and endogenous factors, including environmental enrichment, which increases the production of neurons in juvenile mice and crayfish. The primary goal of the present study was to exploit the spatial separation of the neuronal precursor cell lineage in crayfish to determine which generation(s) of precursors is altered by environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 43 publications
0
29
1
1
Order By: Relevance
“…However, adult neurogenesis in crustaceans is known to be influenced by a number of different factors including environmental conditions, diurnal effects or serotonin levels (reviewed in . Accordingly, for a closer view on proliferative activity and structural complexity of the olfactory system in reptant decapods, we have considered only those studies in which BrdU exposure times included 24 h. Nevertheless, our compilation of data does comprise obvious errors because, for example, we could not assess the ages of the investigated specimens from many of these studies, a factor which also influences the proliferation rate (Schmidt and Harzsch, 1999;Sandeman and Sandeman, 2000;Ayub et al, 2010). What is more, some values had to be estimated from bar graphs (Sandeman and Sandeman, 2000) and were coarsely rounded.…”
Section: Does the Proliferation Rate Correlate With The Complexity Ofmentioning
confidence: 99%
“…However, adult neurogenesis in crustaceans is known to be influenced by a number of different factors including environmental conditions, diurnal effects or serotonin levels (reviewed in . Accordingly, for a closer view on proliferative activity and structural complexity of the olfactory system in reptant decapods, we have considered only those studies in which BrdU exposure times included 24 h. Nevertheless, our compilation of data does comprise obvious errors because, for example, we could not assess the ages of the investigated specimens from many of these studies, a factor which also influences the proliferation rate (Schmidt and Harzsch, 1999;Sandeman and Sandeman, 2000;Ayub et al, 2010). What is more, some values had to be estimated from bar graphs (Sandeman and Sandeman, 2000) and were coarsely rounded.…”
Section: Does the Proliferation Rate Correlate With The Complexity Ofmentioning
confidence: 99%
“…Enriched environments have been shown to increase the number of new cells in the brains of mammals, of course, both in the hippocampus [Kempermann et al, 1997; for a review, see Kempermann et al, 2010] and, if the olfactory environment was enhanced, in the olfactory bulb [Rochefort et al, 2002;Rochefort and Liedo, 2005]. They have also been shown to increase neurons in the brains of crustaceans [Ayub et al, 2010], insects [Scotto-Lomassese et al, 2000], and fish [Dunlap, 2016]. A recent study also showed enhancement in pigeons given an enriched environment [Melleu et al, 2016], but only in the hippocampus; other areas of the telencephalon showed no effect or even a decrease in cells.…”
Section: Is the Production Of New Cells In The Brains Of Adult Amphibmentioning
confidence: 99%
“…Also in insects and crustaceans adult, neurogenesis can be affected by environmental stimulation (Hansen and Schmidt, 2001;Scotto-Lomassese et al, 2002;Ben Rokia-Mille et al, 2008;Ghosal et al, 2009;Ayub et al, 2011). In crickets, adult neurogenesis is regulated by sensory inputs, responsible for cell cycle acceleration, and by hormonal levels, affecting the recruitment of progenitors cells (Cayre et al, 2005a(Cayre et al, , 2005b.…”
mentioning
confidence: 99%
“…The enriched sensory and social conditions, characterized by the simulation of the wild life, enhance the number of mushroom bodies neuroblasts in housed crickets (Scotto-Lomassese et al, 2000), while the ablation of them implies a damage of learning capabilities (Scotto-Lomassese et al, 2003). Also among the crayfishes, the proliferative potential of the neuronal stem cells can be increased enhancing the quality of the environment of housed animals (Sandeman and Sandeman, 2000;Ayub et al, 2011). Sandeman and Sandeman (2000) showed that animals kept with their sibling in large tanks have a higher number of neurons with respect to animals housed alone in small tanks, furthermore cell body size and their survival result increased.…”
mentioning
confidence: 99%